2004
DOI: 10.1055/s-2004-815920
|View full text |Cite
|
Sign up to set email alerts
|

Iodotrimethylsilane-Mediated Cross-Aldol Condensation: A Facile Synthesis of α,α′-Bis(substituted benzylidene)cycloalkanones

Abstract: A facile and efficient method for the preparation of a,a¢-bis(substituted benzylidene)cycloalkanones is described for the first time using iodotrimethylsilane generated in situ from chlorotrimethylsilane and sodium iodide in acetonitrile. The reaction proceeds rapidly at room temperature, giving high yields of products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…In connection with a project in our laboratory, we required mono-2-arylidene derivatives of ketones, particularly of piperidone. The ideal choice in our case is to form the mono-2-arylidene structural unit via a ClaisenSchmidt condensation between the parent ketones and aryl aldehydes [16][17][18][19]. However, this method employs a relatively strong base such as a metal hydroxide or metal alkoxide, so it is often accompanied by side reactions and it offers narrow substrate diversity.…”
Section: Open Accessmentioning
confidence: 99%
“…In connection with a project in our laboratory, we required mono-2-arylidene derivatives of ketones, particularly of piperidone. The ideal choice in our case is to form the mono-2-arylidene structural unit via a ClaisenSchmidt condensation between the parent ketones and aryl aldehydes [16][17][18][19]. However, this method employs a relatively strong base such as a metal hydroxide or metal alkoxide, so it is often accompanied by side reactions and it offers narrow substrate diversity.…”
Section: Open Accessmentioning
confidence: 99%
“…To the best of our knowledge, this is one of the few examples [18,19] in which cross-Aldol condensation of ketones with aldehydes, is carried out at room temperature to give enones. We found that CH 3 CN is more effective solvent in terms of yields than other solvents tested such as CHCl 3 , THF and EtOH.…”
Section: Resultsmentioning
confidence: 99%
“…[5] Different complexes of metal(II) ions have also been used as catalysts, but the yields were less than 38%. [6] In other cases, Cp 2 TiPh 2 , [7] BOMPTO [bis(p-ehtoxyphenyl)telluroxide], [8] RuCl 3 , [9] SmI 3 , [10] Cp 2 ZrH 2 , [11] TiCl 3 (SO 3 CF 3 ), [12] KFÁAl 2 O 3 , [13] FeCl 3 , [14] BF 3 ÁOEt 2 , [15] InCl 3 , [16] TMSCl=NaI, [17] Yb(OTf) 3 , [18] I 2 [19] , TCT [20] , NaOAc=HOAc, [21] and NKC-9 (polymer-supported sulfonic acid) [22] have also been used to promote the reaction. However, these methods have some drawbacks such as use of costly catalysts and toxic reagents and special catalyst preparation.…”
Section: Synthesis and Fluorescence Properties Of αα′-Bis(substitutementioning
confidence: 99%